The effect of aircraft seat pitch on comfort. (October 2020) - Anjani, Shabila; Li, Wenhua; Ruiter, Iemkje A.; Vink, Peter
Abstract: This study explores the relationship between seat pitch and comfort, and the influencing factors, like space experience and anthropometric measurements. Two hundred ninety-four participants experienced economy class seats in a Boeing 737 with 28-inch, 30-inch, 32-inch and 34-inch seat pitches. Anthropometric measurements of the participants were measured. Participants completed a questionnaire on comfort (10-scale), discomfort (CP-50) and space experience and the results were analysed using SPSS 25. This study showed a significant relationship between seat pitch and comfort as well as discomfort. Additionally, it was found that the mean rank of discomfort of each pitch size for the middle seat was higher than the window and aisle seat, though seat pitch did affect the (dis)comfort more compared with seat location. It was also found that anthropometric sizes significantly affect the (dis)comfort on smaller pitch sizes, and all space experience questions had a correlation to the pitch sizes. Highlights: A significant relationship was found between seat pitch and comfort as well as discomfort. The mean discomfort of each pitch size for middle seat was higher than the window and aisle seat, though seat pitch did affect more the (dis)comfort in comparison to seat location. Comfort will rapidly decrease for people with larger body dimensions in shorter seat pitch. Space experience is a psychological factor is relevant for the comfort of passengers.